Endovascular Treatment of Traumatic Pseudoaneurysm of the Superficial Temporal Artery. (April 2016) - Cvetic, Vladimir Zoran; Radmili, Oliver; Lukic, Borivoje; Colic, Momcilo; Davidovic, Lazar
Pseudoaneurysms of the superficial temporal artery (STA) are rare vascular lesions that mainly occur after blunt head trauma. Diagnosis can be made on clinical grounds and is confirmed by ultrasonography. They are usually treated by open surgery procedures, but when the aneurysm is located in inaccessible areas, catheter embolization can be an alternative therapeutic option. We describe a case of a traumatic pseudoaneurysm of the STA which was treated with the vascular plug embolization. We conclude that endovascular embolization can be an option in the treatment of STA pseudoaneurysms.